2018
DOI: 10.3389/fpls.2018.01186
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Phosphate Starvation Response AP2/ERF Gene From Physic Nut in Arabidopsis Alters Root Morphological Traits and Phosphate Starvation-Induced Anthocyanin Accumulation

Abstract: Physic nut (Jatropha curcas L.) is highly tolerant of barren environments and a significant biofuel plant. To probe mechanisms of its tolerance mechanisms, we have analyzed genome-wide transcriptional profiles of 8-week-old physic nut seedlings subjected to Pi deficiency (P-) for 2 and 16 days, and Pi-sufficient conditions (P+) controls. We identified several phosphate transporters, purple acid phosphatases, and enzymes of membrane lipid metabolism among the 272 most differentially expressed genes. Genes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 66 publications
(90 reference statements)
0
39
1
1
Order By: Relevance
“…Pi deficiency may induce anthocyanin accumulation via regulation of the expression of structural genes in the flavonoid pathway by miR399d and PHT1;4 . Similar ideas were previously tested through studies of adaptive responses in the dfr (tt3) and phi1 mutants of Arabidopsis (Leong et al, ; Z. Q. Wang et al, ), wild‐type Arabidopsis (Y. Chen et al, ; Ito et al, ), cultured grape cells (Yin et al, ) and tomato (Tominaga‐Wada et al, ). We hypothesize that MYB regulation of anthocyanin accumulation is associated with Pi status in red Malus leaves and that it induces the expression of the miR399d and PHT1;4 module during Pi starvation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Pi deficiency may induce anthocyanin accumulation via regulation of the expression of structural genes in the flavonoid pathway by miR399d and PHT1;4 . Similar ideas were previously tested through studies of adaptive responses in the dfr (tt3) and phi1 mutants of Arabidopsis (Leong et al, ; Z. Q. Wang et al, ), wild‐type Arabidopsis (Y. Chen et al, ; Ito et al, ), cultured grape cells (Yin et al, ) and tomato (Tominaga‐Wada et al, ). We hypothesize that MYB regulation of anthocyanin accumulation is associated with Pi status in red Malus leaves and that it induces the expression of the miR399d and PHT1;4 module during Pi starvation.…”
Section: Discussionmentioning
confidence: 78%
“…Ethylene‐responsive factors (ERFs) serve either as activators or repressors of ethylene‐mediated transcription. In Arabidopsis, downregulation of the JcERF035 gene increased anthocyanin biosynthesis in aerial tissues of plants under low Pi conditions (Y. Chen et al, ). Strigolactone (SL) treatment induces root hair elongation, anthocyanin accumulation, activation of acid phosphatase, and reduces plant weight, which are characteristic responses to Pi starvation.…”
Section: Introductionmentioning
confidence: 99%
“…The AtERF4 and AtERF8 double-mutant reduces the light-induced anthocyanin contents in Arabidopsis [65]. Under low-isoelectric point conditions, the anthocyanin contents in Arabidopsis lines that overexpress JcERF035 decrease compared with the controls [21]. Here, a phylogenetic analysis found that PbERF22 and PyERF3 were clustered together in one clade ( Figure S2b).…”
Section: Pberf22 Responses To Jasmonate and Ethylene And Is Correlatementioning
confidence: 81%
“…MdERF1B regulates anthocyanin biosynthesis by interacting with MdMYB9 and MdMYB11 in apple [20]. The down-regulation of JcERF035 accelerates anthocyanin accumulation under low-phosphate conditions in Arabidopsis [21]. PyERF3 interacts with MYB114 and forms a new complex with bHLH3 to co-regulate anthocyanin biosynthesis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Plants have evolved a variety of complex responses and adaptations to P deficiency (Muneer and Jeong, 2015; Panigrahy et al, 2009). Notable examples include increasing accumulation of starch and anthocyanin (Chen et al, 2018; Leong et al, 2018; Wang et al, 2015), changing of root morphology and architecture (Gutierrez-Alanis et al, 2018; Li et al, 2016; Suen et al, 2018), enhancing Pi transport activity (Gu et al, 2016; Wang et al, 2017), and inducing endogenous and secreted phosphatases and RNases (Liang et al, 2002; Peng et al, 2018; Tian et al, 2014; Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%